Economic globalization: its manifestations and effects - سعيد, محمد رؤوف; صالح, رفيق محمد (Sulaimani Journal for Humanities, 2001)
There is some thing true that the clossary of (Economic globalization) is not heard from along time but the other truth which. we must explain is that the (Economic globalization) as a phenomenon appeared as a result of interaction of a great number of factors through long period, for instance the effects of scientific and technological revolution and multi-national projects strength as well as the international organizations roles. The most economic development models applied by developing countries failed except the south east Asian countries model which succeed as a result of interaction of the economic globalization factors, therefor the only way to avoid the economic rescind is to accept this phenomenon and deal with it.